2021
DOI: 10.1002/adma.202102525
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Engineered Dzyaloshinskii–Moriya Interaction and Electric‐Field‐Switchable Topological Spin Texture in SrRuO3

Abstract: In situ electrical control of the Dzyaloshinskii–Moriya interaction (DMI) is one of the central but challenging goals toward skyrmion‐based device applications. An atomic design of defective interfaces in spin–orbit‐coupled transition‐metal oxides can be an appealing strategy to achieve this goal. In this work, by utilizing the distinct formation energies and diffusion barriers of oxygen vacancies at SrRuO3/SrTiO3(001), a sharp interface is constructed between oxygen‐deficient and stoichiometric SrRuO3. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 46 publications
(61 reference statements)
2
39
0
Order By: Relevance
“…[32][33][35][36] We would also like to point out that the effects of vacancies and defects have been shown to play a significant role in altering the magnetic properties of various materials. [42][43][44][45] Here, our XRD analysis provides, on a quantitative basis, clearcut evidence that an imbalance of the concentration of vacancies at Fe lattice sites is primarily responsible for the absence of the inversion symmetry. The observation of skyrmions using LTEM and MFM further supports the non-centrosymmetric nature of the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][35][36] We would also like to point out that the effects of vacancies and defects have been shown to play a significant role in altering the magnetic properties of various materials. [42][43][44][45] Here, our XRD analysis provides, on a quantitative basis, clearcut evidence that an imbalance of the concentration of vacancies at Fe lattice sites is primarily responsible for the absence of the inversion symmetry. The observation of skyrmions using LTEM and MFM further supports the non-centrosymmetric nature of the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
“…It is obvious that the magnetization is fully aligned in the negative field direction under the saturation field of −4 T, showing a homogeneous contrast. When the external field is turned towards positive direction, the magnetization starts to reverse with a positive contrast and the homogenous contrast appears at the positive saturated field of 4 T [41,42]. Hence, the magnetic anisotropy switch from the IP to the OOP direction is realized by increasing the SMO layer thickness in the LSMO/SMO superlattices.…”
Section: Thickness Dependence Of the Electric Transport Anisotropy In...mentioning
confidence: 97%
“…The topological Hall effect (THE) as a result of skyrmions is often inferred from the observation of hump-like anomalies in Hall measurements. Several studies have reported the THE in ultrathin SRO heterostructures, which are driven by the strong interfacial Dzyaloshinskii–Moriya interaction (DMI) due to the broken inversion symmetry and spin–orbit coupling. It has been revealed that in a BaTiO 3 (BTO)/SRO heterointerface, ferroelectric-driven ionic displacements in BTO can penetrate into SRO near the interface, resulting in a displacement between Ru and O along the [001] axis. ,, This ferroelectric-driven lattice distortion breaks the inversion symmetry of the SRO structure near the interface, inducing a strong DMI, which is the driving force for the formation of skyrmions.…”
Section: Introductionmentioning
confidence: 99%